SEMIOTIC ANALYSIS ON FENTY BEAUTY’S FOUNDATION ADVERTISING POSTER AS A REPRESENTATIVE OF BEAUTY DIVERSITY - Rachma Prayudawardani, Azahra; Hadiati, Chusni; Muttaqin, Usep (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
This research entitled